The Influence of Tiktok as A Social Media Marketing, Consumer Perceptions, and The Role of Consumer Ethnocentrism on Buying Interest in Local Products (Case Study of MSME Consumers in Yogyakarta) - Muda, Florianus Pruda (Journal of Social Entrepreneurship and Creative Technology, 2024)
This research uses a quantitative approach based on positivist philosophy, specifically utilizing survey-based methods to investigate certain populations or samples. This research aims to dig deeper into data regarding consumers of MSMEs (Micro, Small, and Medium Enterprises) in Yogyakarta. The research methodology involved simple random sampling and incidental sampling to assess the extent to which TikTok, as a social media marketing platform (X1), consumer perceptions (X2), and the role of consumer ethnocentrism (X3) influence purchase intention of local products (Y) among MSME consumers in Yogyakarta. Primary data were obtained through questionnaires filled out directly by respondents, while secondary data came from various sources such as books, journals, and research findings relevant to the object of research. The research population includes TikTok application users who are also MSME consumers in Yogyakarta. Multiple linear regression analysis was used as an analytical tool to reveal the effect of the independent variable on the dependent variable. The results showed that the T-test results confirmed the significant influence of TikTok as a social media marketing platform, consumer perceptions, and the role of consumer ethnocentrism on the purchase intention of local products. The F-test results further reveal that TikTok, consumer perceptions, and consumer ethnocentrism together have a significant influence on the purchase intention of local products among MSME consumers in Yogyakarta.